USAGE OF CONSTRUCTION-ORIENTED SOFTWARE SCAD FOR ANALYSIS OF WORK OF MACHINE-BUILDING STRUCTURES - Bannikov, D. О. (Science and Transport Progress, 2021)
Purpose. In the case of analysis of work of the machine-building structures, the direct usage of construction-oriented software developments is impossible, since ideology and methodology for solving various tasks in construction and machine-building are different. Therefore, in the conducting of practical calculations, there is a need for a certain adjustment of the approaches put in the program complexes and their adaptation to the engineering industry. The presentation of the author's experience of the construction-oriented software SCAD usage for Windows for analyzing the work of various machine-building structures, their components and assemblies is the immediate purpose of the publication. Methodology. During a long period of time the author was engaged in analyzing the work of building, mainly thin-walled, steel structures using the Finite Element Method based on the SCAD for Windows software package. At the same time, a considerable number of machine-building structures were considered, including railroad rolling stock units. Most of these tasks grew into a scientific and research problem that needed to be thoroughly researched and analyzed before giving design recommendations. Findings. The publication presents more than a dozen different tasks, typical for the machine-building industry, which the author had to deal with. Static and quasi-static problems, the problem of motion in time, the contact problem, the problem of the cracks deve-lopment, the physical and geometric non-linearity are among them. Accordingly, for each of these problems the main challenges, features and practical techniques developed during the work are presented, as well as the constructed finite element models are presented as an illustration. Originality. The experience of construction-oriented software product usage on the basis of the Finite Element Method for analyzing of the work of machine-building structures is generalized. A number of practical methods and approaches to the solution of various problems in the machine-building sphere are set forth. Practical value. The application of the given information, methods and approaches allows not only to solve concrete practical problems of the machine-building sphere, but also to obtain correct and practically acceptable solutions.